PEMETAAN ZONA TANGKAPAN IKAN (FISHING GROUND) MENGGUNAKAN CITRA SATELIT TERRA MODIS DAN PARAMETER OSEANOGRAFI DI PERAIRAN DELTA MAHAKAM - Insanu, Radik Khairil (Departemen Teknik Geomatika ITS, 2017)
As a maritime country, Indonesia has a comparative advantage in the potential of marine and fishery resources. The parameters of the distribution of sea surface temperature and the distribution of chlorophyll-a can be used for the determination of the fish catch zone in the Mahakam Delta waters area. By knowing the fishing ground, fishermen can maximize the potentiallity of the fish capture. The purpose of this study was to determine the spatial distribution of ground and chlorophyll-a temperatures and to map potential fishing ground zones. The analysis in this study was determined from the distribution of chlorophyll-a obtained with ATBD 19 MODIS band 10 and 12 algorithms and sea surface temperature distribution on ATBD 25 MODIS bands 20, 31 and 32 using images in March, April, July, September and October 2016. Image processing results obtained, sea surface temperature in March, April, July, September and October averaged 27 ° C to 30 ° C. Only in March the average sea surface temperature has a low temperature. Distribution of chlorophyll-a in 2016 was little identified in September, April and March, whereas in October and July chlorophyll-a was many identified. Determination of high potential catchment zone was having a sea surface temperature of about 27 ° C -30 ° C with high chlorophyll-a value, so that if sea surface temperature and chlorophyll-a conditions were not suitable, it was called a low catchment zone. The low zone of fish catch is scattered to the north and center of the Mahakam delta, as well as in the middle of the makasar strait. The high zone of fish catch is scattered to the south of the Mahakam delta, as well as in the middle of the makasar strait.